Postpartum depression and anxiety among woman attending PNC services at maternirty and women's hospital in Kathmandu, Nepal. - Shrestha, Nisha (2016)
Abstract: Background: Postpartum anxiety disorders and postpartum depression disorders are one of those several mental disorders that produces insidious effects on new mothers, their infant and family. Although mild symptoms of stress and anxiety are expected during the postpartum period, evidence shows that a significant proportion of women manifest symptoms of pathological anxiety and severe depression. Post-partum anxiety refers to any anxiety that is seen in the postpartum period whereas post-partum depression is defined as a non-psychotic depressive state that begins in the post-partum period, after the child birth. The presence of anxiety and depressive symptoms during the postpartum period can have a considerable impact on the psychological health of the mother and endanger the attachment bond that develops with the infant.Thus post-partum period is generally recognized as the time of vulnerability to various affective disorders and the early detection of those disorders is very necessary for preventing the possible negative impacts. Objective: The main aim of the study was to assess the prevalence of postpartum anxiety and depression and the various factors associated with it. Methodology: The design of the study was analytical cross sectional conducted in Paropakar maternity and Women's hospital. Three hundred and seventeen postpartum women met the inclusion criteria and participated in the study. Edinberg Postnatal depression scale and Becks anxiety inventory were used to screen the symptoms of anxiety and depression. A semi-structured questionnaire was also used to collect the necessary information regarding sociodemographic details, maternal characteristics, husband's characteristics and family profile. Bivariate analysis was done to calculate the association between postpartum anxiety and depressive symptoms and other factors. Result: The prevalence of postpartum depression among mothers was 21.5% and the prevalence of anxiety was 12.9%. On bivariate analysis postpartum depression was significantly associated with location (OR=.558, P=.037), ethnicity (OR=.010, P= .470), family type (OR= .391, P= 0.001), Complications during labour (OR=2.023, P= .011), Age of Husband (OR=2.690, P=0.019),Smoking habit of Husband (OR= 2.652, P=.001), Drinking habit of Husband (OR= 2.086, P=.014), Problem due to habits (OR=7.111, P=.000), Child preference (P=.031), History of domestic violence (OR= 9.802, P=0.01) and Presence of husband during delivery (OR=.431, P=.023). Similarly, Postpartum anxiety was significantly associated with a number of variables; Monthly family income (OR=2.372, P=.021), Pregnancy induced health problems (OR= 2.460, P=.024), Complication during labour (OR=2.281, P=.013), History of Miscarriage (OR=2.500, P=.046) , History of anxiety /depression (OR=5.859, P= .004), Problem due to habits (OR=8.579, P= .000), History of domestic violence (OR=5.368, P=.017) and Family care and support during pregnancy (OR=.174, P=.001). Conclusion: The number of postpartum woman experiencing symptoms of anxiety and depression was high. The association of various factors with postpartum anxiety and depression needs to be further explored in future studies. It is recommended that the screening of anxiety and depression should be included in routine antenatal and postnatal care services for its early detection and control.